Metabolic Reprogramming in Gastric Cancer: Trojan Horse Effect - Bin, Yu-Ling; Hu, Hong-Sai; Tian, Feng; Wen, Zhen-Hua; Yang, Mei-Feng; Wu, Ben-Hua; Wang, Li-Sheng; Yao, Jun; Li, De-Feng (Frontiers in Oncology, 2022)
Worldwide, gastric cancer (GC) represents the fifth most common cancer for incidence and the third leading cause of death in developed countries. Despite the development of combination chemotherapies, the survival rates of GC patients remain unsatisfactory. The reprogramming of energy metabolism is a hallmark of cancer, especially increased dependence on aerobic glycolysis. In the present review, we summarized current evidence on how metabolic reprogramming in GC targets the tumor microenvironment, modulates metabolic networks and overcomes drug resistance. Preclinical and clinical studies on the combination of metabolic reprogramming targeted agents and conventional chemotherapeutics or molecularly targeted treatments [including vascular endothelial growth factor receptor (VEGFR) and HER2] and the value of biomarkers are examined. This deeper understanding of the molecular mechanisms underlying successful pharmacological combinations is crucial in finding the best-personalized treatment regimens for cancer patients.